Dampak Kebijakan terhadap Penawaran dan Permintaan Cengkeh Indonesia di Pasar Dunia - Siringoringo, Vina (UNIVERSITAS LANCANG KUNING, 2023)
Clove is a spice plant that plays an important role in Indonesia's economic growth. This study aims to analyze the impact of government policies on demand and supply of Indonesian cloves in the world market. This study uses an econometric approach by building a linear equation model. Data analysis was performed using the Two-Stage Least Square (2SLS) method using the SAS analysis tool version 9.0. The study uses time series data for the period 1985–2019. The increase in the real price of Indonesian cloves, the combination of the increase in the real price of Indonesian cloves with the depreciation of the real exchange rate, the combination of the increase in the real price of Indonesian cloves with the harvested area have an impact on increasing supply, exports, and imports of Indonesian cloves and has an impact on decreasing demand for Indonesian cloves and the real world price of cloves. Real exchange rate depreciation has an impact on increasing exports and increasing imports of Indonesian cloves and has an impact on decreasing demand and supply of Indonesian cloves, decreasing real prices of Indonesian cloves and real world prices of cloves. The increase in harvested area has an impact on increasing supply and demand for Indonesian cloves and on decreasing the real price of Indonesian cloves.